Cost-Effective DDoS Mitigation: Leveraging Nginx Reverse Proxy for Enhanced Server Protection - Pardosi, Victor Benny Alexsius (Universitas Negeri Padang, 2024)
The problem addressed in this research is the vulnerability of servers to Distributed Denial of Service (DDoS) attacks, which lead to disruptions, financial losses, and the loss of user trust due to frequent downtime. To mitigate this issue, a cost-effective solution utilizing Nginx reverse proxy servers was proposed. This research aimed to enhance server resilience against DDoS threats while minimizing operational costs. The primary contribution of this study is the introduction of an innovative approach to DDoS mitigation, emphasizing practical implementation steps. The methodology involved configuring a public server with Nginx and DDoS protection capabilities alongside setting up a private server in an office environment. A reverse proxy using Nginx was deployed to filter incoming traffic and counter DDoS attacks. The main outcomes of the research demonstrate successful mitigation of DDoS attacks, significantly reducing their impact on the private server. Testing on both Layers 3 and Layer 4 confirmed the effectiveness of the approach. The methodology's emphasis on practical implementation steps ensures seamless integration into existing infrastructure. In conclusion, this research offers a practical and budget-friendly solution for organizations seeking to enhance their resilience against DDoS threats. By leveraging Nginx reverse proxy servers, servers lacking dedicated protection can effectively safeguard against DDoS attacks, highlighting the importance of proactive measures in cybersecurity.